Causality for the government budget and economic growth - Afonso, António (2014)
We use a panel of 155 countries for 1970-2010 to study (two-way) causality between government spending, revenue and growth. Our results suggest the existence of weak evidence supporting causality from expenditures or revenues to GDP per capita and provide evidence supporting Wagner’s Law.